Robotic totally endoscopic off‐pump unroofing of left anterior descending coronary artery myocardial bridge: A report of two cases. Issue 8 (18th June 2019) - Mirzai, Saeid; Patel, Brooke; Balkhy, Husam H.
Abstract: Myocardial bridge occurs when the myocardium courses external to an intramyocardial coronary artery, most commonly, the left anterior descending artery. The presentation can range from an asymptomatic, incidental finding to myocardial infarction, and sudden cardiac death. We report two cases of symptomatic MBs, which were treated with surgical unroofing, using a totally endoscopic robotic‐assisted off‐pump approach.